2010
DOI: 10.1186/1471-2458-10-711
|View full text |Cite
|
Sign up to set email alerts
|

Parents' beliefs about appropriate infant size, growth and feeding behaviour: implications for the prevention of childhood obesity

Abstract: BackgroundA number of risk factors are associated with the development of childhood obesity which can be identified during infancy. These include infant feeding practices, parental response to infant temperament and parental perception of infant growth and appetite. Parental beliefs and understanding are crucial determinants of infant feeding behaviour; therefore any intervention would need to take account of their views. This study aimed to explore UK parents' beliefs concerning their infant's size, growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
126
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(136 citation statements)
references
References 29 publications
9
126
0
1
Order By: Relevance
“…In the US, mothers reported that they felt breastfeeding was associated with sleep disturbance (Kennedy et al, 2007) and that having the baby sleep through the night was a major benefit provided by formula (Marchand & Morrow, 1994). Two focus group studies, one of UK women (Redsell et al, 2010) and one of US women (Gross et al, 2010), both found that a need for feeding is parents' preferred explanation for night waking, so they may be less likely to recognise other contributing factors, such as developmental milestones or discomfort. In the UK study, mothers who introduced formula feeds reported being more comfortable with continued night-time crying once they felt confident that the infant was not hungry (Redsell et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the US, mothers reported that they felt breastfeeding was associated with sleep disturbance (Kennedy et al, 2007) and that having the baby sleep through the night was a major benefit provided by formula (Marchand & Morrow, 1994). Two focus group studies, one of UK women (Redsell et al, 2010) and one of US women (Gross et al, 2010), both found that a need for feeding is parents' preferred explanation for night waking, so they may be less likely to recognise other contributing factors, such as developmental milestones or discomfort. In the UK study, mothers who introduced formula feeds reported being more comfortable with continued night-time crying once they felt confident that the infant was not hungry (Redsell et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Two focus group studies, one of UK women (Redsell et al, 2010) and one of US women (Gross et al, 2010), both found that a need for feeding is parents' preferred explanation for night waking, so they may be less likely to recognise other contributing factors, such as developmental milestones or discomfort. In the UK study, mothers who introduced formula feeds reported being more comfortable with continued night-time crying once they felt confident that the infant was not hungry (Redsell et al, 2010). 4 To contextualise maternal decision-making about infant feeding, much more information on women's perceptions of how infant sleep works and the interconnections between sleep and feeding method is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Growth was viewed as a measure of health, 139,223 with insufficient growth being a source of concern for many mothers 131 leading to supplementation with infant formula and/or early weaning to solids. 178,200,222,224 Weight was seen a safety net as illustrated in Kaufman and Karpati's study ("He should be fatter. He's so fragile.…”
Section: Resultsmentioning
confidence: 99%
“…177,178,200,225 The cultural value of heavier children and feeding practices was portrayed in Higgins's study of Puerto Rican families in New York where "mothers often feed babies until they spit up….Lots of mothers feed babies extra milk and put extra sugar and baby foods in a bottle with a big hole in the nipple." (p24) 178 A heavier infant was seen as safer 177 and a sign of good parenting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation